2018
DOI: 10.1155/2018/5971080
|View full text |Cite
|
Sign up to set email alerts
|

All-Trans Retinoic Acid Enhances Matrix Metalloproteinase 2 Expression and Secretion in Human Myeloid Leukemia THP-1 Cells

Abstract: All-trans retinoic acid (ATRA) is an effective drug for the induction therapy of acute promyelocytic leukemia. However, the treatment is associated with adverse events such as retinoic acid syndrome (RAS) in some patients, whose histologic characteristics included organ infiltration by leukemic cells. Matrix metalloproteinase 2 (MMP-2) is often upregulated in tumor cells and plays a role in tumor cell migration and invasion by degrading the extracellular matrix. In this study, we examined the possible modulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 66 publications
2
12
1
Order By: Relevance
“…Similarly, our results revealed that the use of an RARα agonist moderately induces CPD protein expression, even at higher concentrations, whereas combined treatment with an RARα agonist and an RXRα agonist significantly induced CPD expression, suggesting that the RAR-RXR complex is required to induce the transcriptional activation of CPD expression. Similar to current observations, our previous study showed that ATRA enhances MMP-2 expression and secretion in THP-1 cells in an RAR/RXR-dependent manner (Vu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, our results revealed that the use of an RARα agonist moderately induces CPD protein expression, even at higher concentrations, whereas combined treatment with an RARα agonist and an RXRα agonist significantly induced CPD expression, suggesting that the RAR-RXR complex is required to induce the transcriptional activation of CPD expression. Similar to current observations, our previous study showed that ATRA enhances MMP-2 expression and secretion in THP-1 cells in an RAR/RXR-dependent manner (Vu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…*P < 0.05 vs. DMSO. Skidgel, 2001) and our previous study demonstrated that dexamethasone, an anti-inflammatory drug, inhibits ATRAinduced MMP-2 secretion in THP-1 cells (Vu et al, 2018), we tested whether this drug can also suppress ATRA-induced CPD expression and secretion in THP-1 cells. ATRAinduced enhancement of CPD mRNA expression ( Fig.…”
Section: Rar/rxrmentioning
confidence: 98%
“…The inhibition of the Src-YAP-IL6 axis in both cell lines leads to reduced migration and invasion [21]. A similar pro-metastatic effect was observed in THP-1 human myeloid leukemia cells in which ATRA induced MMP-2 expression and secretion in a calcium ion-dependent manner, via the retinoic acid receptor (RAR) and retinoid X receptor (RXR) signaling pathways [22].…”
Section: All-trans Retinoic Acidsmentioning
confidence: 74%
“…Despite the beneficial effects of carotenoids against metastasis in various cancer types, the use of carotenoids in some cases can lead to pro-invasive behavior, as demonstrated by ATRA use in cancer treatment [ 21 , 22 ]. Therefore, a more precise evaluation of carotenoid efficacy and the determination of detailed mechanisms can support a better understanding of carotenoids’ anti-cancer properties, especially in cancer prevention and therapy, for safe, efficient, and timely clinical trials.…”
Section: Carotenoids In Cancer Metastasismentioning
confidence: 99%
See 1 more Smart Citation